The effect of two types of ankle orthoses on the repetitive rebound jump performance - Masanori Morikawa (BMC Sports Science, Medicine and Rehabilitation, 2022)
Abstract Background Ankle orthotics decreases the maximal vertical jump height. It is essential to maximize jump height and minimize ground contact time during athletic performance. However, the effect of ankle orthotics on athletic performance has not been reported. We aimed to investigate the effect of ankle orthotics on squat jump (SJ), countermovement jump (CMJ), and repetitive rebound jump (RJ) performance. Methods Twenty healthy volunteers performed SJ, CMJ, repetitive RJ under no-orthosis and two orthotic conditions (orthosis 1 and orthosis 2). During SJ and CMJ, we measured the vertical ground reaction force and calculated the following parameters: jump height, peak vertical ground reaction force, rate of force development, net vertical impulse, and peak power. During repetitive RJ, the jump height, contact time, and RJ index were measured. A two-dimensional motion analysis was used to quantify the ankle range of motion in the sagittal plane during SJ, CMJ, and repetitive RJ. Results Multivariate analysis of variance and the post hoc test showed orthosis 2 significantly decreased in the vertical jump height (p = 0.003), peak power (p = 0.007), and maximum plantarflexion and dorsiflexion angles (p < 0.001) during SJ Ankle orthoses 1 and 2 did not influence to the RJ performance compared to those using the no-orthosis condition. Additionally, orthosis 2 significantly decreased the jump height at the end of repetitive RJ (p = 0.046). Conclusions These results suggest that ankle orthosis do not affect average RJ performance but should be considered when performing repetitive jumps frequently.